Modes of death in patients with heart failure and preserved ejection fraction. (1st February 2017) - Aschauer, Stefan; Zotter-Tufaro, Caroline; Duca, Franz; Kammerlander, Andreas; Dalos, Daniel; Mascherbauer, Julia; Bonderman, Diana
Abstract: Background: Recent studies suggest that reduced right ventricular function is an important predictor of outcome in patients with heart failure and preserved ejection fraction (HFpEF). Because affected patients suffer from a broad spectrum of non-cardiac co-morbidities, it remains unclear, whether they actually die from right heart failure (RHF) or as a consequence of other conditions. Methods: Consecutive patients with a confirmed diagnosis of HFpEF were enrolled in this prospective registry. Local and external medical records, as well as telephone interviews with relatives were used to ascertain modes of death. RHF was accepted as a mode of death, if the following criteria were met: 1. right ventricular dysfunction assessed by transthoracic echocardiography, and 2. clinical signs of right heart decompensation at the time of death. Results: Out of 230 patients with complete follow-up, 16.5% ( n = 38) died after a mean of 30 ± 17 months. 60.5% deaths were classified as cardiovascular and 34.2% as non-cardiovascular. In 5.3% patients, the reason for death remained unknown. Of the cardiovascular cases ( n = 23), 91.4% of deaths were attributed to RHF, 4.3% died from stroke and 4.3% from sudden cardiac death. Of the non-cardiovascular deaths ( n = 13), 46.2% of deaths were attributed to major infections and 38.4% deaths were related to cancer. Other reasons for death included ileus (7.7%) and major bleeding (7.7%). Conclusion: In our well-characterised HFpEF cohort, more than half of all deaths could directly be attributed to RHF. The right ventricle seems to be a meaningful therapeutic target in a subset of patients.